Persepsi Masyarakat Betawi terhadap Ondel-Ondel sebagai Atribut Pengamen Jalanan di Petukangan Utara Jakarta Selatan - Umam, Choirul; Simatupang, Sunengsih (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
One of the typical Betawi arts is Ondel-ondel. Ondel-ondel are large dolls in pairs, made from woven bamboo, wearing masks and palm fiber hair. This research uses intercultural adaptation theory to change the current view of Ondel-ondel which is used as an attribute of busking. This research uses descriptive qualitative analysis methods. Researchers conducted interviews consisting of five informants. The research was carried out purposively, with the aim of obtaining data that could be used in discussions. The conditions set for selecting speakers are the Betawi people who live in the North Petukangan area. The results of research entitled Betawi Community Perceptions of Ondel-ondel as an Attribute of Street Buskers in North Petukangan, South Jakarta. This research has found and extracted information from all data which includes data based on interviews with sources. Four of the five sources that researchers interviewed, of the four sources, had two perceptions, some were positive and negative. This research shows that through interviews consisting of 3 points in the research, the existence of Ondel-ondel buskers in the community, there are those who think positively that it is considered cultural preservation, but there are also those who think negatively that Ondel-ondel buskers 3on the street are also considered to damage the reputation of Betawi culture. and the presence of Ondel-ondel buskers on the street can disrupt street order.